(untitled) (Journal of Parents and Teachers, 2014)
Educational research aims to motivate students during their study of science, and for this, more and more ICT resources are being used. Thus, this article offers databases, word processors, presentation programs, simulation and communication to work in an attractive way the Natural Sciences.